Economic Pluralism in the Study of Wage Discrimination: A Note - Nick Drydakis (Global Labor Organization (GLO), 2018)
Economic pluralism proposes that economists and social planners should consider alternative theories to establish a range of policy actions. Neoclassical, Feminist and Marxian theories evaluate well-grounded causes of wage discrimination. Racist attitudes, uncertainties regarding minority workers' productivity and power relations in lower-status sectors might generate discriminatory wages. Each cause deserves corresponding policy action. Given pluralism, wage discrimination might be reduced by implementing equality campaigns, creating low-cost tests to predict workers' productivity and abolishing power relations towards minority workers. Pluralism might be jeopardised if there is a limited desire to engage with less-dominant theoretical frameworks. Also, pluralism might be misled with rejection of dominant theories.
Keywords: B4; B5; B54; J71; 330; Economic Pluralism; Schools of economic thought; Wages; Discrimination